Tsetse, trypanosomiasis and cattle in a changing environment - Bourn, D.M.; Milligan, K.; Wint, W. (International Livestock Centre for Africa, 1986)
Identifies interrelationships between modifications of the environment and the growth of Nigeria's population and consequent agricultural expansion in the subhumid zone resulting in the disappearance of habitats & hosts of tsetse. Discusses impacts of these changes in the distribution of the national cattle herd, particularly in relation to incidence of tsetse & trypanosomiasis.